Atresio oesophagi: odlozené chirurgické riesenie dlhého segmentu - Vidiscák, M; Smrek, M (Rozhledy v chirurgii, 2001)
Atresia of the long segment of the oesophagus in children and its surgical treatment is frequently very complicated and is associated with a high rate of complications. The authors present a patient with a long segment of oesophageal atresia type Vogt IIIB. The distance between the oral and aboral stump was 4 cm. During the first session the authors made a thoracotomy, separated the aboral stump from the trachea and closed the opening in the trachea as well as the distal stump. Then they approximated both stumps without attempting an anastomosis and fixed them by stitches to the spine. They closed the chest and performed a gastrostomy. After eight weeks they repeated the thoracotomy and made an oesophago-oesophago end-to-end anastomosis. The patient was subjected after operation three times to balloon dilatation on account of a stricture at the site of anastomosis. He is now 18 months after operation and has no complaints and no stricture.
Keywords: Esophagus; Infant, Newborn; Catheterization; ezofágus; mužské pohlaví; Anastomosis, Surgical; lidé; atrézie jícnu; Male; anastomóza chirurgická; Trachea; katetrizace; trachea; reoperace; Esophageal Atresia; Humans; Reoperation; novorozenec